Among Persons With Multiple Sclerosis (MS), Objective Sleep, Psychological Functioning, and Higher Physical Activity Scores Remained Stable Over 2 Years—Results From a Small Study Under Naturalistic Conditions - Sadeghi Bahmani, Dena; Gonzenbach, Roman; Kesselring, Jürg; Bansi, Jens; Motl, Robert W.; Cordier, Dominik; Rothen, Oliver; Niedermoser, Daryl; Gerber, Markus; Brand, Serge (Frontiers in Psychiatry, 2020)
Background: Persons with multiple sclerosis (PwMS) are at increased risk to report poor sleep patterns and lower physical activity indices. To date, data on longitudinal objectively sleep assessment is missing. In the present study, we investigated, the pattern of objective sleep and subjective physical activity indices over a period of 13.5 months, under naturalistic conditions. Method: 13.5 months after their first assessment, a total of 16 PwMS (M-age = 49.13 median EDSS score: 5; 11 females) were re-assessed on their objective sleep via portable sleep-electroencephalogram (EEG-)-devices, along with their subjective sleep patterns physical activity indices, psychological functioning, and MS-related information. While the baseline assessment was performed in a rehabilitation center, the follow-up assessment to place at participants’ their naturalistic and familiar setting. Results: Statistically, symptoms of depression and fatigue, subjective sleep, and physical activity levels did neither increase, nor decrease over time, although descriptively, both moderate and vigorous physical activity levels decreased, and fatigue and subjective insomnia increased. Time awake after sleep onset statistically significantly decreased, while light sleep duration increased by trend. Conclusions: Among a smaller sample of PwMS, objective sleep in their naturalistic setting remained fairly stable over a mean time lapse of 13.5 months after clinic discharge. Physical activity levels descriptively decreased. The present results are of clinical and practical importance for treatment counseling: PwMS can be reassured that their sleep quality does not deteriorate, once they have left a rehabilitation center. Further, they should be encouraged to keeping their physical activity levels as stable as possible.